PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK BERBASIS GRAPHIC ORGANIZER GUNA MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA PADA MATERI IPAS KELAS IV - Mu’arief Hasanah; Fathur Rokhman; Suwito Eko Pramono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the characteristics and analyze the feasibility, practicality, and effectiveness of graphic organizer-based pop-up book learning media. The problems found in the field are the lack of student participation in the science and science learning process, which is caused by the application of conventional teaching methods, little activity and interaction in class, and less emphasis on the application of science or knowledge, so that students' scientific literacy is low. This research uses a Research & Development (R & D) research design with a 4D model (define, design, develop, and disseminate). The research results showed that pop-up book learning media based on graphic organizers was declared very feasible with an average result of 4.83 material experts and 4.58 media experts. The graphic organizer-based pop-up book learning medium was stated to be very practical by teachers and students, with an average score of 96%. Apart from that, pop-up book learning media based on graphic organizers are able to improve students' scientific literacy skills in science material. This is proven by the results of the N-Gain test, which obtained a score in the experimental class of 0.7 with high criteria. Meanwhile, the control class also showed an increase of 0.6 with moderate criteria. This shows that improving learning outcomes in the experimental class is more effective than in the control class. Apart from that, the results of the independent sample t test show that the sig. (2-tailed) 0.011 < 0.05, so it can be concluded that the application of graphic organizer-based pop-up book learning media can increase students' literacy.